The Rapid Fibrin Plate – a Method for Plasminogen Activator Assay - Marsh, N. A; Gaffney, P. J (Thrombosis and Haemostasis, 1977)
Most of the technical problems associated with the fibrin plate method have been overcome in recent years with the exception of the long incubation period. This study was carried out to investigate plasminogen-enrichment as a means of shortening this period.Fibrin plates made up to contain 2.0 casein units of added plasminogen each, were opaque, firm, did not lyse spontaneously and yielded biometrically-valid parallel-line assays for streptokinase and urokinase after a 3 hour incubation period. Urokinase assays were more accurate than those for streptokinase probably because of the latter’s shallow dose-response curve. Plasminogen-enrichtment appears therefore to be a convenient way of producing a “rapid” fibrin plate requiring incubation for 3 hours compared with the usual 16 to 20 hours.